Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.51 Example continued

None of the standard Laplace transforms on frame 6.44 equals s/(s2+α2)2s/(s^{2}+\alpha^{2})^{2}. To complete the problem, we use the following result.

Theorem.

Suppose the Laplace transform of f(x)f(x) converges for all s>s0s>s_{0} and equals F(s)F(s). Then the Laplace transform of xf(x)xf(x) exists for all s>s0s>s_{0} and (xf(x))=-dFds{\mathcal{L}}(xf(x))=-\frac{dF}{ds}. Hence -1(dFds)=-x(F){\mathcal{L}}^{-1}(\frac{dF}{ds})=-x{\mathcal{L}}(F).

Now

s(s2+α2)2=-12dds(1s2+α2).\frac{s}{(s^{2}+\alpha^{2})^{2}}={-\frac{1}{2}\frac{d}{ds}\left(\frac{1}{s^{2}% +\alpha^{2}}\right).}

Using the Theorem, we see that the solution to the problem is the inverse Laplace transform of s(s2+α2)2\frac{s}{(s^{2}+\alpha^{2})^{2}}, which is

12x-1(1s2+α2)=12αxsinαx.{\frac{1}{2}x{\mathcal{L}}^{-1}\left(\frac{1}{s^{2}+\alpha^{2}}\right)=}\,{% \frac{1}{2\alpha}x\sin\alpha x.}